2004
DOI: 10.1242/jeb.01022
|View full text |Cite
|
Sign up to set email alerts
|

Oxidants, antioxidants and the ischemic brain

Abstract: SUMMARY Despite numerous defenses, the brain is vulnerable to oxidative stress resulting from ischemia/reperfusion. Excitotoxic stimulation of superoxide and nitric oxide production leads to formation of highly reactive products,including peroxynitrite and hydroxyl radical, which are capable of damaging lipids, proteins and DNA. Use of transgenic mutants and selective pharmacological antioxidants has greatly increased understanding of the complex interplay between substrate deprivation and ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
369
1
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(383 citation statements)
references
References 156 publications
(137 reference statements)
3
369
1
10
Order By: Relevance
“…60 -64 Such injury is mediated by reactive oxygen and nitrogen species, including the superoxide ion, hydrogen peroxide, hydroxyl radical, nitric oxide, and peroxynitrite, 61,63,65 Glutamate-mediated excitotoxicity, which leads to an increase in intracellular calcium, induces several endogenous enzymes that produce free radicals, including nitric oxide synthase, xanthine oxidase, and the phospholipase A 2 -cyclooxygenase pathway. 63 Such changes in intracellular calcium also perturb mitochondrial function, leading to leakage of superoxide.…”
Section: Oxidative Damagementioning
confidence: 99%
“…60 -64 Such injury is mediated by reactive oxygen and nitrogen species, including the superoxide ion, hydrogen peroxide, hydroxyl radical, nitric oxide, and peroxynitrite, 61,63,65 Glutamate-mediated excitotoxicity, which leads to an increase in intracellular calcium, induces several endogenous enzymes that produce free radicals, including nitric oxide synthase, xanthine oxidase, and the phospholipase A 2 -cyclooxygenase pathway. 63 Such changes in intracellular calcium also perturb mitochondrial function, leading to leakage of superoxide.…”
Section: Oxidative Damagementioning
confidence: 99%
“…Peroxynitrite (ONOO − ) is a reactive nitrogen species known to increase after ischemia/ reperfusion [11,12]. Peroxynitrite is generated by the nonenzymatic reaction between superoxide and nitric oxide and modifies proteins via several different mechanisms, including protein S-nitrosation and nitration of tyrosine residues.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Purified PDHC is highly sensitive to inactivation by exposure to hydroxyl radicals [5]. It is not known, however, whether inactivation occurs after exposure to other forms of oxidative stress, e.g., nitric oxide and peroxynitrite, that are generated at abnormally high levels shown to promote postischemic neuronal injury during ischemic reperfusion [9,10].Peroxynitrite (ONOO − ) is a reactive nitrogen species known to increase after ischemia/ reperfusion [11,12]. Peroxynitrite is generated by the nonenzymatic reaction between superoxide and nitric oxide and modifies proteins via several different mechanisms, including protein S-nitrosation and nitration of tyrosine residues.…”
mentioning
confidence: 99%
“…Actually, asphyxiated brains often demonstrate apoptotic neuronal death (6). Additionally, it was recently found that in the early stage after hypoxic-ischemic (HI) insult, reactive oxygen species (ROS), such as nitric oxide and hydroxyl radicals, contribute to apoptotic neuronal death (7)(8)(9)(10)(11). ROS, which are induced by oxidative stress, are an important factor in initiating DNA peroxidation, which can directly trigger DNA fragmentation and thereby initiate apoptosis (12).…”
mentioning
confidence: 99%